Do working parents in the United States expect work location to impact job and family satisfaction in the post-pandemic period? Evidence from a survey experiment - Moller, Stephanie; Ruppanner, Leah; Yavorsky, Jill E. (Frontiers in Sociology, 2024)
The pandemic response allowed many parents in the United States and globally to work remotely for the first time ever which, for many, continued into the recovery. It is unclear whether, after a period when a large segment of the United States labor force worked remotely, remote work is viewed favorably or unfavorably among employed parents. We present results from a survey experiment assessing whether employed parents in the United States perceive that remote work will impact a hypothetical employed parents’ job and family satisfaction and, critically, whether perceptions of work–family conflict and anticipated job rewards mediate this relationship. We find that respondents who are also employed parents perceive that hypothetical employed parents who access remote work will report lower job satisfaction and higher family satisfaction. Perceptions of work–family conflict do not mediate this association. Rather, we find that job rewards (e.g., pay, promotion, etc.) fully mediate the relationship between remote work and perceived job satisfaction. Ultimately, this indicates that employed parents perceive that remote work will bring workers like them less pay and thus lower job satisfaction but greater family satisfaction. This extends arguments about remote work in the light of the conceptualization of a flexibility stigma and a flexibility paradox. Implications for practice and theory are discussed.